Functional complexity of the Leishmania granuloma and the potential of in silico modeling - Moore, John; Moyo, Daniel; Beattie, Lynette; Andrews, Paul; Timmis, Jon; Kaye, Paul (Frontiers in Immunology, 2013)
Abstract In human and canine visceral leishmaniasis and in various experimental models of this disease, host resistance is strongly linked to efficient granuloma development. However, it is unknown exactly how the granuloma microenvironment executes an effective antileishmanial response. Recent studies, including using advanced imaging techniques have improved our understanding of granuloma biology, at the cellular level, highlighting heterogeneity in granuloma development and function, and hinting at complex cellular, temporal and spatial dynamics. In this mini-review, we discuss the factors involved in the formation and function of L.donovani-induced hepatic granulomas, as well as their importance in protecting against inflammation-associated tissue damage and the generation of immunity to rechallenge. Finally, we discuss the role that computational, agent-based models may play to answer outstanding questions within the field.